Genetic polymorphisms of endothelial marker, connexin and acyl-CoA genes among ethnic Malay subjects with essential hypertension - Salim, Elnaz (2020)
Hypertension is a complex multifactorial disorder that is thought to result from an interaction between an individual’s genetic background and various lifestyle also environmental factors. Essential hypertension (EH) are majority of hypertensive cases and diagnosed where there is no clear evidence of medical condition predisposing to the high blood pressure. There have been variety of genetic studies is relation to hypertension and some of them showed association with occurrence of hypertension. Family of Endotheline1 (EDN-1) and Endothelin converting enzyme (ECE) vasoconstricting peptide produced by vascular endothelial. Recent studies proposed that there was significant difference between EDN-1 lys198Asn(rs5370) and ECE (rs212526) with essential hypertension. As well as, Connexin gene family (Cxs) belong to the large family of gap junction that are involved in many physiological disorders like that hypertension. Cx37(C1019T) and Cx40+71 A/G were candidate gene for this study. Moreover, Acyl-CoA synthetase medium-chain family member3(rs886433) also another gene was determined in this study. The main objective of this study was to determine the candidate gene polymorphism and gene expression involved in essential hypertension among Malay subjects. Since, there have been variety of genetic association studies of EDN1, ECE, Cx37-40 and ACMS3 conducted on different population, however no study was done on Malaysia populations and in relation to hypertension. Genetic polymorphism and gene expression are serve as molecular biomarkers for the detection of the individual at risk of developing the disease. This association study included 177 of subjects without EH as control and 97 of subjects with EH as case. Extraction genomic DNA was done all subjects. Cx40 and Cx37 gene polymorphism was detected using Polymerase Chain reaction (PCR) followed by Restriction Fragment Length Polymorphism (PCR- RFLP). The PCR products were digested with EcorI and DrdI restriction enzyme at 65°c for 20 min. the RFLP products were detected using 3% agarose gel electrophoresis. ACMS3, EDN1 and ECE gene were detected by real time PCR (RT- qPCR) with Taq-Man probes. Genotype and allele frequencies in case and control samples were compared by using Chi-Square test while clinical characteristic parameters and social-demographic background was analyzed using descriptive static. Furthermore, in this study, the expression profile of Acyl CoA enzyme (ACMS3) which involved in human fatty acid biosynthesis was analyzed. Real time PCR was carried out using RNA extracted from 50 cases as well as 50 control subjects. Relative analyzed was used to determined level of gene expression. The demographic characteristic of the subjects including age, body mass index (BMI), systolic blood pressure (SBP), diastolic blood pressure (DBP),low density lipoprotein(LDL), triglyceride (TG) and Cholesterol level were shown to be differentially significant (p<0.05) in the case subject when compared to control groups. HDL did not show any significance. The results of this study were show that the genotypes and allele frequencies of C1019T Cx37, +71Cx40 A/G, ET-1 rs5370 G/T and ACMS3 A/G gene were highly significant in hypertensive subjects as compared to the healthy (p<0.05). while SNP of ECE gene C/T did not significantly (P>0.05) when compared to control group. In gene expression demonstrated significant differences between expression of ACMS3gene at the mRNA level in patients with hypertension compare with control group. Hence, this candidate genes as possible genetic biomarker and risk factor for EH in Malay subjects.